Performance of rapeseed-mustard in India- a temporal analysis (Journal of Oilseed Brassica, 2026)
The performance of rapeseed-mustard in India using time series data from 1967-68 to 2019-20 was examined. The total period was divided into period I, II and III to analyze the trends, compound annual growth rate (CAGR), decomposition analysis, instability analysis and impact of technological change in production of rapeseed-mustard. The study revealed that performance of rapeseed-mustard during different periods was noteworthy. An upward increasing trend was evidenced for area, production and yield in all the three periods signifying the progress of rapeseed-mustard while the CAGR analysis revealed acceleration for area, production and yield. The decomposition analysis indicated that change in production of rapeseed-mustard were due to yield effect and area effect during period I; area expansion during period II and; area effect and yield effect during period III. The crop was relatively stable with lower instability with regard to area, production and yield resulting to sustained production. Technological progress on production of rapeseed-mustard was observed in periods I and III, while area expansion contributed to production growth in all the three periods. Technology regress was not evidenced in rapeseed-mustard indicating the power of technology(s) developed under the National Agricultural Research and Education System. To increase the production of rapeseed-mustard, technology assemblage is warranted in high area-low productivity districts; diversification to newer agro-eco regions and in selected rice-fallow ecosystems. To task strides towards “Make in India” and “Atmanirbhar Bharat”, focus on value chains is important towards doubling of farmers income and for promoting rural entrepreneurship.